Prise en compte de la diversité végétale arborée chez les paysagistes - Brice Dacheux-Auzière; Audrey Marco; Yves Petit-Berghem (Projets de Paysage)
This article focuses on the relation between arborescent plant diversity and the landscape project in the literature of the history of gardens published during the last three centuries. The study if these documents has made it possible to identify four major “eras” which not only contributed to changing the way of thinking about and designing projects, but also integrated and used the arborescent plant as a defining component in the development of major parks and private domains from the 17th century up until today, and which have now become public and urban spaces. Thus, from the 17th to the 20th century, spanning from the art of classic gardens to the trend of functional urbanism, the article shows how it is possible to identify the parameters relating to forms of organisation, structure and practise which point to the early presence of tree diversity. The objective is to place within the historical framework this natural element present in cities as a vector of and/or a support for biodiversity.